Periodontal status of tooth adjacent to implant with peri-implantitis. (March 2018) - Sung, Cheng-En; Chiang, Cheng-Yang; Chiu, Hsien-Chung; Shieh, Yi-Shing; Lin, Fu-Gong; Fu, Earl
Abstract: Objectives: To evaluate the relationship between peri-implantitis and the periodontal health of the adjacent tooth, the periodontal status of the teeth adjacent and contralateral to the implants with and without peri-implantitis. Methods: Fifty-three subjects with existing dental implants and chronic periodontitis were examined in this cross-sectional study. Seventy implants were categorized into peri-implantitis (n = 42) and healthy/mucositis (n = 28) groups. The periodontal and peri-implant status, including probing depth (PD), clinical attachment level (CAL), and gingival recession (GR) were measured at 6 sites around the implants and the teeth adjacent and contralateral to those implants. In total 560 sites of the 70 teeth/implant sets, the association between the periodontal status at the near and away sites of the teeth (according to implant) and the implant status (without/with peri-implantitis) was examined. Results: A significantly different mean PD (5.01 ± 1.69, 4.42 ± 1.8, 3.55 ± 0.88, and 3.71 ± 1.07 mm, p <  0.001) and CAL (6.02 ± 2.36, 4.89 ± 2.04, 4.35 ± 1.11, and 4.35 ± 1.5 mm, p <  0.001) were noted at the near sites of the teeth adjacent to the implants with peri-implantitis when compared with the away sites of adjacent and contralateral teeth and the near sites of contralateral teeth. With generalized estimating equation (GEE), the presence of peri-implantitis (β  = 1.041 mm, confidence interval = 0.646–1.435, and p <  0.001; β  = 0.857 mm, confidence interval = 0.279–1.434, and p <  0.004) and tooth location (β  = 0.65 mm, confidence interval = 0.4–0.9, and p <  0.001; β  = 0.682 mm, confidence interval = 0.34–1.024, and p <  0.001) were significantly associated with the values of the PD and CAL of the teeth. Moreover, the factor of examining sites (i.e. near and away sites of the tooth) was significantly associated with CAL (β = 0.304 mm, confidence interval = 0.019–0.588, and p  = 0.036) and GR (β = 0.136 mm, confidence interval = 0.02–0.252, and p  = 0.022). Conclusion: The existence of peri-implantitis, the tooth location, and the examining site are significantly associated with the periodontal measurements of the remaining teeth. Clinical significance: Peri-implant health is related to the periodontal health of the natural teeth close to the dental implant.